(untitled) (Biological Sciences - PJSIR, 2024)
The growth and productivity of different varieties of beetroot Beta vulgaris were examined in presence of urea, nitrogen, phosphorus, potassium, compost and salt during the field trial, and the chemical constitution of three different varieties, dark red, ruby queen and detroit-2 was identified quantitatively by spectrophotometer. Ruby queen shows maximum growth as compared to dark red and detroit-2. The application of urea, nitrogen, phosphate, potassium and compost reduces the amount of catalase and total anti- oxidant enzymic potensial while increasing the concentrations of proteins, lipids, and sugars, with high growth and yield. Maximum growth was observed in the presence of urea, while the application of salt inhibited growth in all three varieties. In the nitrogen, phosphorus, potassium and compost-treated plants, nitrogen, phosphorus, and potassium show more growth as compared to compost. Similarly, metabolic contents such as IAA, chlorophyll and phenolic, were found in high concentrations in urea, nitrogen, phosphorus, potassium and compost-treated plants as compared to salt-treated plants.